Six priorities to advance the science and practice of coral reef restoration worldwide. Issue 8 (20th September 2021) - Vardi, Tali; Hoot, Whitney C.; Levy, Jessica; Shaver, Elizabeth; Winters, R. Scott; Banaszak, Anastazia T.; Baums, Iliana B.; Chamberland, Valérie F.; Cook, Nathan; Gulko, David; Hein, Margaux Y.; Kaufman, Les; et al.
Abstract : Coral reef restoration is a rapidly growing movement galvanized by the accelerating degradation of the world's tropical coral reefs. The need for concerted and collaborative action focused on the recovery of coral reef ecosystems coalesced in the creation of the Coral Restoration Consortium (CRC) in 2017. In March 2020, the CRC leadership team met for a biennial review of international coral reef restoration efforts and a discussion of perceived knowledge and implementation bottlenecks that may impair scalability and efficacy. Herein we present six priorities wherein the CRC will foster scientific advancement and collaboration to: (1) increase restoration efficiency, focusing on scale and cost‐effectiveness of deployment; (2) scale up larval‐based coral restoration efforts, emphasizing recruit health, growth, and survival; (3) ensure restoration of threatened coral species proceeds within a population‐genetics management context; (4) support a holistic approach to coral reef ecosystem restoration; (5) develop and promote the use of standardized terms and metrics for coral reef restoration; and (6) support coral reef restoration practitioners working in diverse geographic locations. These priorities are not exhaustive nor do we imply that accomplishing these tasks alone will be sufficient to restore coral reefs globally; rather these are topics where we feel the CRC community of practice can make timely and significant contributions to facilitate the growth of coral reef restoration as a practical conservation strategy. The goal for these collective actions is to provide tangible, local‐scale advancements in reef condition that offset declines resulting from local and global stressors including climate change.